Strategi Pengembangan Usaha Dalam Meningkatkan Pendapatan Pada Rumah Makan Purnama Raya H. Salsabila Lebak Bandung Jelutung - Misni Saifudin; Addiarrahman Addiarrahman; Lidya Anggraeni (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The purpose of this study was conducted to examine three issues, namely: (1) Business development strategy for Purnama Raya H. Salsabila Restaurant Lebak Bandung Jelutung,(2) Obstacles faced by Purnama Raya H. Salsabila Lebak Restaurant Bandung Jelutung, (3) Islamic economic view towards the business development strategy of Purnama Raya H. Salsabila Restaurant, Lebak Bandung Jelutung. To reveal these three issues in depth and comprehensively, the authors used a field research method with a qualitative approach with primary and secondary data sources by interviewing 10 people, namely the restaurant and consumers. From the results of this study it can be concluded that: Padang Surya Restaurant in the city of Mukomuko has implemented a business development strategy, namely the strategy includes: product strategy, price strategy and sales strategy. Islamic Economic Review of the business of Purnama Raya H. Salsabila Restaurant, Lebak Bandung Jelutung, is appropriate with Islamic principles.